STRATEGI MENINGKATKAN MOTIVASI GURU MELALUI SISTEM RAPOR - Alenda Nabil Julia; Iwan Siswanto (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the principal’s strategy in improving teachers’ work motivation through the implementation of a teacher report card system at PKBM Tahfiz At-Tamam Pekanbaru. This research employs a qualitative approach with a descriptive method to gain an in-depth understanding of the implementation process of the teacher report card as a form of performance evaluation that influences teachers’ work motivation. Data were collected through interviews, observations, and documentation involving the principal and five teachers selected using a purposive sampling technique. The results show that the structured and continuous implementation of the teacher report card functions not only as an evaluation tool but also as feedback that can enhance teachers’ discipline, responsibility, and professionalism. In addition, the teacher report card also serves as a motivational instrument through rewards, coaching, and competency development. However, the implementation of this system also creates perceived pressure among some teachers due to performance assessment demands. The novelty of this study lies in its focus on a performance evaluation strategy based on the teacher report card in a non-formal educational institution, which has not been widely studied, particularly in relation to improving teachers’ work motivation through the managerial approach of the school principal.